2011
DOI: 10.1093/cvr/cvr104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of activation of endothelial nitric oxide synthase mediated by transient receptor potential vanilloid type 1

Abstract: TRPV1 activation in ECs may trigger Ca(2+)-dependent PI3K/Akt/CaMKII signalling, which leads to enhanced phosphorylation of TRPV1, increased TRPV1-eNOS complex formation, eNOS activation and, ultimately, NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
123
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 35 publications
8
123
0
1
Order By: Relevance
“…Moreover, our results regarding the non-LKB1 AMPKK function of CaMKII in TRPV1 ligand-induced activation of AMPK/eNOS signaling are consistent with previous studies of caffeine-elicited fatty acid uptake and oxidation, and puerarin-increased eNOS phosphorylation mediated through a CaMKII/AMPK signaling pathway (31,32). Recently, growing evidence has suggested that the TRPV1 channel plays an important role in the activation of eNOS activation and eNOS-related cardiovascular diseases such as hypertension and atherosclerosis (7,8). TRPV1 activation by capsaicin leads to increased phosphorylation of protein kinase A (PKA) and eNOS in ECs and improved vasorelaxation and reduced blood pressure in hypertensive rats (7 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, our results regarding the non-LKB1 AMPKK function of CaMKII in TRPV1 ligand-induced activation of AMPK/eNOS signaling are consistent with previous studies of caffeine-elicited fatty acid uptake and oxidation, and puerarin-increased eNOS phosphorylation mediated through a CaMKII/AMPK signaling pathway (31,32). Recently, growing evidence has suggested that the TRPV1 channel plays an important role in the activation of eNOS activation and eNOS-related cardiovascular diseases such as hypertension and atherosclerosis (7,8). TRPV1 activation by capsaicin leads to increased phosphorylation of protein kinase A (PKA) and eNOS in ECs and improved vasorelaxation and reduced blood pressure in hypertensive rats (7 …”
Section: Discussionsupporting
confidence: 92%
“…This notion was further supported by our findings that in parallel to the eNOS activation, exposing ECs to evodiamine markedly increased the physical interaction of TRPV1 with eNOS and AMPK. Thus, apart from its channel function, TRPV1 may function as a scaffold for the recruitment and formation of a complex encompassing eNOS and kinases, and these proteinprotein interactions may also be critical for the regulation of eNOS activity, which agrees with our previous finding of TRPV1 ligands promoting the formation of the TRPV1-Akt-CaMKII-eNOS complex in ECs (8). These findings strongly indicate that kinase-dependent regulation and protein-protein interaction may work in concert to promote eNOS activation and NO production in response to TRPV1 ligands in ECs.…”
Section: A M P K I N T R P V 1 -M E D I a T E D E N O S A C T I Vsupporting
confidence: 91%
See 2 more Smart Citations
“…Activation of eNOS‐NO signaling is suggested to be a major mechanism of clinical therapeutic drugs in treating cardiovascular diseases 26, 27, 28. eNOS can be activated by physiological and metabolic stimuli, such as shear stress and clinical therapeutic drugs, and result in NO production.…”
Section: Discussionmentioning
confidence: 99%